The Apollo 5' exonuclease functions together with TRF2 to protect telomeres from DNA repair - Lenain, Christelle; Bauwens, Serge; Amiard, Simon; Brunori, Michele; Giraud-Panis, Marie-Josèphe; Gilson, Eric (Current biology, 2006)
A major issue in telomere research is to understand how the integrity of chromosome ends is preserved . The human telomeric protein TRF2 coordinates several pathways that prevent checkpoint activation and chromosome fusions. In this work, we identified hSNM1B, here named Apollo, as a novel TRF2-interacting factor. Interestingly, the N-terminal domain of Apollo is closely related to that of Artemis, a factor involved in V(D)J recombination and DNA repair. Both proteins belong to the beta-CASP metallo-beta-lactamase family of DNA caretaker proteins. Apollo appears preferentially localized at telomeres in a TRF2-dependent manner. Reduced levels of Apollo exacerbate the sensitivity of cells to TRF2 inhibition, resulting in severe growth defects and an increased number of telomere-induced DNA-damage foci and telomere fusions. Purified Apollo protein exhibits a 5'-to-3' DNA exonuclease activity. We conclude that Apollo is a novel component of the human telomeric complex and works together with TRF2 to protect chromosome termini from being recognized and processed as DNA damage. These findings unveil a previously undescribed telomere-protection mechanism involving a DNA 5'-to-3' exonuclease.